Propositional calculus and binary calculus (ESP) - Skliar, Osvaldo (1990)
We present an efficient method of propositional calculus which allows the manipulation of logical functions with an arbitrary number of propositional variables. This method is base on the use of binary sequences (in other words, sequences of digits which can only be either 0 or 1) and certain operation between them. This calculus is then implemented by using neural network type devices.